Knowledge, attitude, and practice related to COVID-19: A comparison between patients with mental illness and the general population in Qatar - Suhaila Ghuloum; Ibrahim Makki; Yassin Hassan Eltorki; Oraib Abdallah; Fahad Farhan Alanzy; Mohamed Adil S. Khoodoruth; Mohamed F. Ali; Hassen Al-Amin (Frontiers in Psychiatry, 2022)
BackgroundIn 2020, the World Health Organization (WHO) declared COVID-19 a global health pandemic. The rapid spread and high fatalities associated with COVID-19 have increased interest in assessing Knowledge, Attitude, and Practice (KAP) toward this illness among the general population in comparison to specific subgroups. Most publications to date have explored KAP among the general public, healthcare providers, and people with chronic conditions, but not amongst those with mental illness. Yet, research has shown patients with mental illness are at higher risk of poor outcomes related to infectious diseases such as COVID-19. The objective of this study is to compare KAP toward COVID-19 between people with mental illness and the general public.Materials and methodsThis is a cross-sectional study, done over 3°months in 2020, to compare KAP during the COVID-19 pandemic in three groups: outpatients from outpatient Psychiatry clinics (N = 165), inpatients admitted to a Psychiatry ward (N = 100), and the general public (N = 345). KAP parameters were assessed through online surveys.ResultsThe proportion of subjects in the public group (84.8%) giving the correct responses to most Knowledge questions was significantly higher than those in the inpatient and outpatient groups. Compared to the public and inpatient groups, subjects in the outpatient group (92.7%) were significantly more optimistic and confident that COVID-19 would be brought under control. A higher proportion of subjects from the general public (82.9%) indicated that they attended crowded places and were more compliant in wearing masks. Multiple linear regression analyses showed that poorer COVID-19 knowledge was associated with being single and having a young age (18–29), with both inpatients and outpatients and with primary-or secondary-level education.ConclusionPatient populations, both inpatients and outpatients, had inadequate Knowledge, more positive attitudes and confidence regarding the outcome of COVID-19, and less safe practices than the public. This highlights the need for targeted approaches around COVID-19 and pandemics in general in this vulnerable population.